THE ROLES OF MAJELIS TAKLIM NURUL HUDA IN STRENGTHENING RELIGIOUS CHARACTERS AND SOCIAL CARE IN BONE REGENCY - Sarifa Halija; Andi Rasdiyanah; Amrah Kasim; Andi Marjuni; Sarifa Suhra (Al-Qalam, 2021)
This paper examined the roles of Majelis Taklim Nurul Huda in strengthening religious characters and social care in Bone Regency. This type of research was qualitative, located in Nurul Huda mosque, the largest mosque in Bajoe, the capital of Tanete Riattang Timur District, Bone Regency. The primary data source was obtained from the management of Majelis Taklim Nurul Huda, and the secondary data was obtained from a variety of relevant articles. Data were collected through interviews, observations, and document searches. The research instruments were the observation guidelines, interview guides, and documentation tools. Data analysis was carried out in three stages which are data reduction, data exposure, conclusion and verification. The results showed that the roles of Majelis Taklim Nurul Huda in strengthening religious characters are seen in the members and the surrounding community have a deep faith, diligent worship, and noble characters. Meanwhile, the positive impact of the development of Majelis Taklim in shaping the character of social care appears in facilitating social activities.